Reconciliation Narratives:The Birth of a Nationafter the US Civil War - Esposito, Elena; Rotesi, Tiziano; Saia, Alessandro; Thoenig, Mathias (American Economic Review, 2023)
We study how the spread of the Lost Cause narrative—a revisionist and racist retelling of the US Civil War—shifted opinions and behaviors toward national reunification and racial discrimination against African Americans. Looking at screenings of The Birth of a Nation, a blockbuster movie that greatly popularized the Lost Cause after 1915, we find that the film shifted the public discourse toward a more patriotic and less divisive language, increased military enlistment, and fostered cultural convergence between former enemies. We document how the racist content of the narrative connects to reconciliation through a “common-enemy” type of argument. (JEL J15, L82, N31, N32, N41, Z13)